2015
DOI: 10.1186/s40201-015-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of honking impact on traffic noise in urban traffic environment of Nagpur, India

Abstract: BackgroundIn context of increasing traffic noise in urban India, the objective of the research study is to assess noise due to heterogeneous traffic conditions and the impact of honking on it.MethodTraffic volume, noise levels, honking, road geometry and vehicular speed were measured on national highway, major and minor roads in Nagpur, India.ResultsInitial study showed lack of correlation between traffic volume and equivalent noise due to some factors, later identified as honking, road geometry and vehicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 17 publications
0
28
1
1
Order By: Relevance
“…The peak noise level is manageable to some extent because it is almost behavioural and originates mainly due to honking, sudden acceleration and deceleration of vehicles. Vijay et al reported that no honking may reduce the traffic noise level by 2 to 5 dB(A) at the microenvironment [18]. Significantly L 50 , the median noise level had ambiguous relationship with both background and peak noise component but the degree of linearity was higher with the background noise component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak noise level is manageable to some extent because it is almost behavioural and originates mainly due to honking, sudden acceleration and deceleration of vehicles. Vijay et al reported that no honking may reduce the traffic noise level by 2 to 5 dB(A) at the microenvironment [18]. Significantly L 50 , the median noise level had ambiguous relationship with both background and peak noise component but the degree of linearity was higher with the background noise component.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the Indian cities and towns like Visakhapatnam, Kolhapur, Asansole and Balasore have also been facing serious traffic noise pollution in last few decades due to substantial growth of new vehicles, low turnover of old vehicles, inadequate road network and urbanization [13–16]. Assessment of traffic noise level is difficult in Indian cities due to the heterogeneity in traffic and environmental conditions e.g., mixed vehicle types, congestion, road conditions, frequent honking and lack of traffic sense [17, 18]. Therefore, it is important to consider such diverse factors in monitoring and assessment of traffic noise level in the Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the implementation of mentioned noise control approach, there is a possibility of further decrease in the overall noise level in the study area. The traffic congestion on the existing highways and the haulage road is expected to be reduced and subsequently the noise generated due to honking will come down by 3-5 dB(A) (Vijay et al, 2015). Thus, with this mitigation measure, the anticipated overall noise levels in the study area are within the permissible limits of CPCB and EPA as well.…”
Section: Noise Mitigationmentioning
confidence: 95%
“…Thus, it would seem appropriate to strive a balance between the complexity of the problem and accuracy in final results as enunciated by King et al [53]. Eventually, adopting a comprehensive approach with inclusion of many input variables like distances, height of building, road surface type, streetaspect ratio, honking effect [54], vegetation, type of locality, presence of industries nearby [55] etc. shall be helpful in developing a practical model for Delhi roads.…”
Section: Implications Of Developed Modelsmentioning
confidence: 99%